Sundressed : natural fabrics and the future of clothing - Tonti, Lucianne (Island Press, 2023)
"In this superbly written book, fashion insider Lucianne Tonti looks beyond sustainable fashion to a future remade by natural fibres. An exploratory dive into the art and industry of clothing and an ode to the possibilities in nature, Sundressed is an accessible, engaging and optimistic challenge to designers, farmers and business to think bigger.If we grasp their potential, natural fabrics will revolutionize more than the way we dress. Regenerative farming of fibres like cotton, wool, flax and cashmere can restore biodiversity, soils and water cycles, making it possible to create beautiful clothes while improving the environment. Tonti introduces the farms and fashion houses that are changing the industry. She uncovers a growing hive of activity worldwide, from mulberry groves in China and cotton collectives in California to Mongolian goatherds and Australian sheep farmers. Tonti's extensive research in sustainability is interwoven with her insights and personal experiences in fashion houses internationally. With a designer's eye for detail and an insider's understanding of the market, Tonti shows us where our clothes come from and why it matters."--Provided by publisher.